RISK MANAGEMENT PRACTICES IN THE INSURANCE INDUSTRY BY CONSIDERING SUPPLY CHAIN MANAGEMENT - balchat, Baqer ali; jabbar abed, Iftehar (International Journal of Supply Chain Management, 2019)
Abstractâ?? Risk management leads to more informed decision making, coherent planning and better use of resources; Risk management helps companies achieve their financial and strategic goals in the face of the risks posed by the permanent complexity of the global economy. Given the rapid pace of global developments and the resulting various uncertainties in supply chain operations have made that supply chain risk management is a very important issue today. Given that supply chain risk management has a great impact on the stability of the relationship between partners in the supply chain, therefore, a decision-making model for supply chain risk management helps to solve the supply chain issues considerably. In this paper decision-making model based on product lifecycle, operational cycle, and operational factors of the organization are presented for insurance risk management. The main purpose of this study is to identify the factors affecting supply chain risk and to measure its effects in the insurance industry of the country. This paper has been a descriptive-correlational research and has used multiple regression analysis techniques and path analysis to determine the factors affecting the supply chain risk.